Personalized treatment suggestions: the validity and applicability of the risk-prevention-index social in low back pain exercise treatments - Wippert, Pia-Maria; Puschmann, Anne-Katrin; Drießlein, David; Banzer, Winfried; Beck, Heidrun; Schiltenwolf, Marcus; Schneider, Christian; Mayer, Frank (Journal of Clinical Medicine, 2020)
Background: The back pain screening tool Risk-Prevention-Index Social (RPI-S) identifies the individual psychosocial risk for low back pain chronification and supports the allocation of patients at risk in additional multidisciplinary treatments. The study objectives were to evaluate (1) the prognostic validity of the RPI-S for a 6-month time frame and (2) the clinical benefit of the RPI-S. Methods: In a multicenter single-blind 3-armed randomized controlled trial, n = 660 persons (age 18–65 years) were randomly assigned to a twelve-week uni- or multidisciplinary exercise intervention or control group. Psychosocial risk was assessed by the RPI-S domain social environment (RPI-SSE) and the outcome pain by the Chronic Pain Grade Questionnaire (baseline M1, 12-weeks M4, 24-weeks M5). Prognostic validity was quantified by the root mean squared error (RMSE) within the control group. The clinical benefit of RPI-SSE was calculated by repeated measures ANOVA in intervention groups. Results: A subsample of n = 274 participants (mean = 38.0 years, SD 13.1) was analyzed, of which 30% were classified at risk in their psychosocial profile. The half-year prognostic validity was good (RMSE for disability of 9.04 at M4 and of 9.73 at M5; RMSE for pain intensity of 12.45 at M4 and of 14.49 at M5). People at risk showed significantly stronger reduction in pain disability and intensity at M4/M5, if participating in a multidisciplinary exercise treatment. Subjects at no risk showed a smaller reduction in pain disability in both interventions and no group differences for pain intensity. Regarding disability due to pain, around 41% of the sample would gain an unfitted treatment without the back pain screening. Conclusion: The RPI-SSE prognostic validity demonstrated good applicability and a clinical benefit confirmed by a clear advantage of an individualized treatment possibility.